Effectiveness of Bacillus Calmette–Guérin (BCG) Vaccine as Post-exposure Prophylaxis Against Leprosy Among Household Contacts: A Systematic Review - Habiburrahman Al Ghifari; Yasmin Mazaya Bil Haqq; Atania Ilma (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Indonesia remains one of the top three countries with the highest leprosy burden. Current prevention focuses mainly on early detection. However, limited public awareness allows continued transmission, especially among household contacts (HHCs). Considering WHO’s 2030 “Toward Zero Leprosy” goal, post-exposure prophylaxis (PEP) with vaccines represents a promising strategy. Although no specific leprosy vaccine exists, Bacillus Calmette–Guérin (BCG) provides cross-protection due to antigenic similarity with Mycobacterium  leprae. Its effectiveness is assessed through new leprosy cases and IgM anti-phenolic glycolipid-1 (PGL-1) antibody levels. Therefore, this systematic review aims to evaluate the effectiveness of BCG vaccination as post-exposure prophylaxis against leprosy among household contacts. Methods: Databases including PubMed, Springer, Nature, Frontier, Epistemonikos, ScienceDirect, BMJ, Sage, and Karger were searched. From 6,303 records, seven studies met inclusion criteria. Eligible studies were RCTs and cohort studies (2015–2025) on BCG-based PEP among household contacts. Non-English, in vitro, review, and non-field case reports were excluded. Study quality was assessed using JBI Critical Appraisal tools.Results and Discussion: Seven studies showed that BCG vaccination reduced leprosy incidence by 57–75%. The strongest protection occurred with BCG revaccination (59–95%), while combining BCG with single-dose rifampicin (SDR) achieved about 80% efficacy. Immunologically, vaccinated contacts showed lower IgM anti-PGL-1 levels, indicating a protective immune response. This indicates the vaccine’s ability to simulate a protective immune response that suppresses the humoral response against Mycobacterium leprae.Conclusion: BCG vaccination provides substantial protection as post-exposure prophylaxis against leprosy, while its revaccination or combination with SDR further strengthens preventive efficacy among household contacts.